Pengaruh Semangat Kerja dan Disiplin Kerja Terhadap Produktivitas Karyawan Pada PT. Sinar Galesong Pratama Malalayang - Pangkey, Max (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: Problems as well as a goal of this study was to determine how much influence the morale and discipline of the productivity of employees working at PT. Sinar Pratama Galesong Malalayang. Respondents involved in this study were the number of employees is 30 people. Data were collected using questionnaires techniques and then analyzed by using multiple linear regression analysis with the help of SPSS version 14. The results showed that both variables Morale and Discipline Work has a very strong relationship at all to the Work Productivity in the Primary Galesong PTSinar employees Malalayang. Based on these results, it is suggested to the Chairman at PT. Primary Galesong rays should maintain discipline in particular work to employees in terms of timeliness, the ability to do a good job and have a high responsibility in work. With the increased labor discipline as mentioned above is expected that employees will be able to work well and vigorously so that the objectives of the company can be achieved. Keywords: morale, work discipline, employee productivity.